Global Positive Effects of ICT Usage and Adoption in SMEs: A Literature Review Prior to the COVID-19 Crisis - Sujit Kumar Basak; Marguerite Wotto; Paul Bélanger (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
The Covid - 19 has certainly increased the uses of Information and Communication Technology (ICT) in all domains. Despite this, ICT had become an integral part of Small and Medium Enterprises (SMEs) that are the backbones of a nation’s economic development. This article’s objective is to analyze the global positive effect of ICT uses and adoption in SMEs across the world before the Covid - 19. Consequently, a systematic literature review methodology was used based on a few steps, namely, formulation of review questions, search strategy devising, study selection criteria, quality appraisal criteria, and finally design of studies to select and download 220 articles before 2020. Out of them, a total of 85 most significant and well-informing article’s analysis is conducted. The results showed ICT has positive impacts on SMEs production and performance in the world (Asia, Africa, Europe, Australia, Oceania, North America, and South America) and it also changes and improves the work mode, technics, and conditions of SMEs. Due to missing data, this research has not included all the countries of each continent. Considering results analysis from all countries would give better outcome.